Rapid Correction of Hypoalbuminemia and Promotion of Granulation Tissue in Pediatric Deep Partial-Thickness Burns via Targeted Immunonutrition: A Case Report - Ni Kadek Ari Puji Astiti; Christian (HM Publisher, 2026)
Background: Pediatric burns induce a profound hypermetabolic and hypercatabolic state, distinct from adults due to limited physiological reserves and high growth demands. The rapid onset of negative nitrogen balance and hypoalbuminemia significantly impairs wound healing and immune function. Case presentation: We report the case of a 7-year-old male with pre-existing malnutrition (StrongKids Medium Risk) presenting with 23% total body surface area (TBSA) Grade IIB scald burns affecting the posterior humerus, lumbosacral, gluteus, and femoral regions. The patient exhibited acute hypoalbuminemia (2.3 g/dL) and anorexia due to pain. A specialized medical nutrition therapy (MNT) protocol was implemented using the Curreri Junior formula, targeting 2,500 kcal/day and 105 g protein/day. The intervention utilized a stepwise escalation of polymeric enteral nutrition enriched with immunonutrients (Glutamine, Zinc, and Vitamin C). Despite the severity of the injury, the patient demonstrated rapid nutritional rehabilitation. By day 5 of hospitalization, albumin levels normalized to 3.1 g/dL, and significant granulation tissue formation was observed. The patient achieved a weight gain of 0.4 kg during the acute phase, countering the expected catabolic weight loss. Conclusion: Early, aggressive, and calculated nutritional support incorporating specific immunonutrients can reverse the catabolic effects of thermal injury in pediatric patients. This case highlights the efficacy of the Curreri Junior formula combined with Glutamine and Zinc in accelerating wound closure and correcting biochemical markers in resource-limited settings.